Исследование влияния информативности и точности измерения параметров сигналов на эффективность распознавания типов и режимов работы радиоизлучающих источников - Калюжный, Н. М.; Николаев, И. М.; Попов, А. М.; Колесник, В. И. (ХНУРЭ, 2011)
The results of experimental researches of radiating source recognition algorithms are resulted. Dependences of correct recognition probability on exactness of signal parameter measuring are certain as a result of the conducted researches. The got results allow to choose the most effective recognition algorithms and produce the grounded requirements to exactness of signal parameter measuring.
Keywords: источники радиоизлучения; средства радиоконтроля